PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS X SMA - Yerizon Yerizon (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2021)
The purpose of this study was to produce learning tools based on Realistic Mathematics Education (RME) that were valid, practical and effective to improve the mathematical problem solving abilities of class X SMA / MA students. The learning tools developed are the Learning Implementation Plan (RPP) and Student Worksheets (LKPD). This research is a development research with the Plomp model which consists of three stages, namely the preliminary research, the development stage, and the assessment stage. At the development stage, the design and assessment of learning devices is carried out through the stages of formative evaluation. Field test subjects involved in this study were students of class X SMAN 5 Padang, West Sumatra. The instruments used were RPP validation sheets, LKPD validation sheets, teacher response questionnaires, student response questionnaires. Before the instrument is used to collect data, it is validated by mathematicians, linguists, and educational technologists. The results of the analysis of the RPP and LKPD validation sheets show that the learning tools developed are valid. Learning tools are classified as practical based on the results of the analysis of teacher response questionnaires, student response questionnaires, and learning implementation observation sheets. In addition, the learning tools developed are also effective for improving students' mathematical problem solving abilities based on test results.